Incorporating innovations into organizations functioning: virtual versus traditional firm - Korsakiene, Renata; Tvaronavičius, Vytautas; Tvaronavičienė, Manuela (Business: Theory and Practice, 2006)
The aim of the paper is to reveal specific features of functioning of virtual organizations in order to suggest directions of efficient management in traditional firms. Specific features of virtual organizations are classified and compared to those of traditional ones. The authors suggest the ways enabling to incorporate innovation into management of traditional organization in order to achieve more efficient performance of latter ones.